Community’s knowledge, attitude and practices towards inclusive home based early childhood education in Uganda: Lessons for scaling deep - Ejuu, Godfrey; Locoro, Victor; Nandera, Miria; Omoding, Martin; Mafabi, Lenard W.; Kutosi, George W.; Kharono, Irene (South African Journal of Childhood Education, 2022)
Most innovations that would help to provide inclusive home-based early learning for children in marginalised communities sometimes collapse when the funders pull out. One of the reasons for this has been lack of information on the dynamics in such communities that can help to sustain such innovations. Aim: This study aimed to provide information on what communities in the study area know, their attitude and practices that can sustain home-based early learning initiatives. Setting: The study setting was in rural districts with marginalised communities, two in eastern and the other two in central Uganda. Methods: This study uses an exploratory approach to collect data through interviews and focus group discussions in the selected Ugandan communities. Data were collected from 120 purposively sampled parents, caregivers and teachers using in-depth interviews. Results: (1) Participants support the establishment of inclusive home learning centres and already have learning expectations of their children by the age of 6 years. (2) While women are more available for early childhood care services, men are supportive of inclusive education. (3) Cases of children with special needs are more prevalent in the study area, suggesting that many more could be found than currently known. Conclusion: The study concludes that communities have preferences for some activities carried out in the centres if established. This study provides an advance information that is useful for planning by agencies and government departments that may want to support establishment of such centres in marginalised communities.
Keywords: Inclusive home based early childhood education; Access; Centre based care; Scaling; Community support